Exchange and Interest Rates prior to EMU: The Case of Greece - Angelos A. Antzoulatos; Bernd Wilfling (Hamburg Institute of International Economics (HWWA), 2003)
Recently a variety of exchange and interest rate models capturing the dynamics during the transition from an exchange rate arrangement of floating rates into a currency union have been derived. While these stochastic equilibrium models in continous time are theoretically rigorous, a systematic and extensive empirical validation is still lacking. Using exchange and interest rate data collected prior to the Greek EMU-entrance on 1 January 2001 this paper tries to fill the gap between theory and real-world data. The analysis reveals that the formal models can explain many features of the Greek exchange and interest rate dynamics on the road to EMU.
Keywords: C52; C51; F33; F31; E43; 330; exchange and interest rate models; policy shifts; economic regime switching models; Wechselkurs; Zins; Volatilität; Europäische Wirtschafts- und Währungsunion; Wechselkurstheorie; Stochastischer Prozeß; Zinsparität; Zinsstrukturtheorie; Schätzung; Griechenland